Analisis Konsep Pajak Dalam Kitab Al-Kharaj Abu Yusuf : Implementasi Pada Sistem Perpajakan Kontemporer - Afifah Irwan; Hana Tuo (CV. ITTC INDONESIA, 2024)
Tax is one of the sources of state revenue that is formally used to sustain the development of a country. In this case, taxes can be said to be the main pillar of development, including to finance civil servants, buy combat equipment, build infrastructure, and others. Unfortunately, the tax taken from the people is often misused in its implementation as a support for development and is only enjoyed by a handful of people. Abu Yusuf, an economic thinker and faqih in the Abasid dynasty, has written this tax theory in his book Al- Kharaj which discusses the basis of the tax applied, and the reasons for the use of funds in society so that it can be accounted for. In this study, it will be known things related to taxes applied by Abu Yusuf that can be applied in modern human life today. Regarding the types of taxes and how they are implemented in today's contemporary taxation system. So that it can be a solution for a country to manage its income from taxes and use it as well as possible.